Profil Penggunaan Obat Antibiotik Golongan Penisilin di Apotek Rawat Jalan RSUD Kuala Kurun: Profile of Use of Penicillin Class of Antibiotic in Outpatient Pharmacy at Kuala Kurun Hospital - Nurul Chusna; Guntur Satrio Pratomo; Lisa Murwanda (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the profile of the use of penicillin-class antibiotics in Kuala Kurun Hospital. The method used in this study is the descriptive method, the population in this study were all prescription outpatients that included penicillin group antibiotics at Kuala Kurun Hospital during the period of September-November 2015 totaling 132 prescriptions, all of which were used as samples. Data collection techniques used in the form of documentation is by calculating the use and classifying the antibiotic groups of penicillin based on the type of preparation. Based on the results of the study it was found that the most widely used antibiotic dosage forms in the period September-November 2015 were tablet preparations. The use of Amoxicillin tablets was prescribed for 92 prescriptions with 69.7% usage percentage. Ampicillin tablets are prescribed as many as 18 prescriptions with a usage percentage of 13.6%. Whereas antibiotics in the penicillin group, Amoxicillin syrup preparations total use as many as 22 recipes with a percentage of 16.7%. Based on the visit of patients who came to Kuala Kurun Hospital in the period of September-November 2015 there were 132 prescriptions of patients using penicillin class of antibiotics. After the data is grouped, it is known that the most widely used penicillin antibiotic form is a tablet preparation with Amoxicillin and Ampicillin.